Empirical Modelling of Drying Characteristics of Elongate Glassy Perchlet (Chanda nama) (Hamilton, 1822) in Solar Hybrid Dryer - Alfiya, P. V.; Murali, S.; Delfiya, D. S. Aniesrani; Samuel, Manoj P. (Fishery Technology, 2018)
This study was conducted to evaluate the performanceof solar dryer with electrical back-up toproduce quality dried Glassy perchlet (Chandanama). Insolation of the experimental region variedfrom 25 to 1025 W m-2. Atmospheric temperatureshowed a variation between 29.5 to 34.5Â°C. Relativehumidity outside the dryer ranged from 56 to 76.5%showing a direct relationship with temperature.Drying experiment was carried out for 10 hat drying air temperature of 60Â°C. Relative humidityand velocity of drying air inside the drying chamberwas 68% and 0.8 m s-1 respectively. Dryingconditions were maintained inside the dryer byelectrical back-up. Weight loss of pre-processed C.nama during drying was measured at 1 h duration.Drying characteristic data were fitted into empiricaldrying models. Two-term model was found to be thebest fit for the drying characteristic data underspecified conditions (R2=0.998, RMSE=0.016 andÏ‡2=0.00027).